In Search of “Saner Minds”:: Bishop James Morrison and the Origins of the Antigonish Movement - Remes, Jacob (Acadiensis, 2010)
Abstract The 1925 United Mine Workers strike in Cape Breton was a crucial turning point in the thinking of James Morrison, the bishop of the Catholic Diocese of Antigonish from 1913 to 1950. Before the strike, Morrison had consistently opposed the education reforms promoted by his subordinate, Father J.J. Tompkins. The strike encouraged Morrison to fear radical labor unions, which encouraged him accept the creation of the Extension Department at St. Francis Xavier University. This article, drawing largely on Morrison’s correspondence, traces the evolution of Morrison’s thought within the context of eastern Nova Scotia’s labor history.